Personal Finance Millenial Generation : Determination of Mediation of Investment Intention on the Influence of Investment Knowledge and Returns on Investment Decisions on Gold Instruments in Bekasi City - indra Wahyu putra, Christophorus; Widjanarko, Wirawan; Juan Carlos, Gerry; Indrianna Meutia, Kardinah; Hasanuddin, Hasanuddin; Siagian, Rosalina; Sobari, Mohamad (Dinasti Publisher, 2024)
This research is a study that studies the influence of investment knowledge and returns on investment decisions through investment interest in Bekasi City. This research uses a quantitative approach and population of this study is not known with certainty but the unit of analysis used is investors who invest in gold instruments and are the millennial generation in Bekasi City. This research sample adopted previous research which used the Lemeshow (1997) approach with a sample size of 100 respondents. The results of this research indicate that investment knowledge does not influence investment decisions, return and investment interest influence investment decisions. Meanwhile, the indirect effect found that investment knowledge influences investment decisions through investment interest, while returns do not influence investment decisions through investment interest. This research focuses on the millennial generation and specifically those who invest in gold instruments. This research also focused on the city of Bekasi, which is one of the developing capital cities of Indonesia. The novelty of this research is in the research model where the researcher adds a return variable to this research which has never been done before to the best of the researcher's knowledge.